Beginning Fedora - Sharma, Shashank (Apress, 2012)
Linux has come a long way in a short time. Computing itself is still relatively young by any standard; if the era of modern computing started with the invention of the microchip, it’s still less than 50 years old. But Linux is a youngster compared even to this; it has been around for only 16 of those years. In that brief time span, a student’s personal project has grown to where it now runs many computers throughout the world. It has rampaged through the computing industry, offering an alternative to commercial solutions such as those offered by Microsoft, and toppling long-held beliefs about the way things should be done. This is all by virtue of the fact that Linux is simply better than every other choice out there. Many argue that it’s more secure and faster than other operating systems. But here’s the kicker—Linux is free of charge. Yes, that’s right. It doesn’t have to cost a penny.